THE IMPACTS OF FORMULATION AND STORAGE ON α-GLUCOSIDASE INHIBITORY ACTIVITY OF LEMONGRASS, GINGER, AND BLACK TEA FUNCTIONAL BEVERAGES - Filiana Santoso; Jennifer Sunardi; Florence Ignatia; Maria Dewi Puspitasari Tirtaningtyas Gunawan-Puteri (Sanata Dharma University, 2021)
Functional beverages from lemongrass (Cymbopogon citratus), white ginger (Zingiber officinale Roscoe) and black tea (Camelia sinensis) were developed based on their α-glucosidase inhibitory (AGI) activities and sensory acceptance. The AGI was evaluated using in vitro enzymatic assay, while sensory acceptance was tested using affective sensory tests. The evaluation of their aqueous extracts showed that dried lemongrass and ginger possessed higher extraction yield (3.4 %, 2.7 %, respectively), though not necessarily accompanied with a better AGI activity (IC50 24.50 mg/mL, IC50 16.61 mg/mL) than the fresh lemongrass and ginger (2.1 %, 1.8 %, IC50 17.93 mg/ml, IC50 47.00 mg/mL, respectively). Meanwhile, the evaluation of the combined extract showed additive and synergistic effects. The extract combination formula was selected based on the sensory acceptance, resulting in the beverages containing 4.29 mg/mL of lemongrass, 0.71 mg/mL of ginger, and 1.05 mg/mL of black tea with a total phenolic content of 636.45 mg/L Gallic Acid Equivalent (GAE). The selected formula showed the stability of AGI activity andthe pH value at 4 °C were in accordance with the growth of microbial count that was lower than those stored at 25 °C in a 50-day period. Changes in color and oBrix value were not significantly observed in the samples stored at 25 °C and 4 °C. Lime juice was selected as the additional flavoring agent, which could increase both the palatability and AGI activity of the beverages.